2005
DOI: 10.3201/eid1103.040676
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus RNA in Encephalitis Patient

Abstract: We describe a fatal case of encephalitis that might be correlated with primary human metapneumovirus (HMPV) encephalitis. Postmortem HMPV RNA was detected in brain and lung tissue samples from the patient. Furthermore, HMPV RNA was found in culture fluids from cells coincubated with lung tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 13 publications
5
67
0
3
Order By: Relevance
“…A case report from Germany in 2005 described a 14-mo-old boy who died of encephalitis, and from whom hMPV was identified in brain tissue by PCR and cell culture (37). Subsequent reports by various groups have described patients with encephalitis from whom hMPV was identified in throat or nasal swabs, although infection of the CNS was not established in these cases (38 -40).…”
Section: Human Metapneumovirusmentioning
confidence: 99%
“…A case report from Germany in 2005 described a 14-mo-old boy who died of encephalitis, and from whom hMPV was identified in brain tissue by PCR and cell culture (37). Subsequent reports by various groups have described patients with encephalitis from whom hMPV was identified in throat or nasal swabs, although infection of the CNS was not established in these cases (38 -40).…”
Section: Human Metapneumovirusmentioning
confidence: 99%
“…Several studies demonstrated that HMPV accounts for a major proportion of hospitalizations for lower respiratory tract infections in infants and young children 30,47,50 . The most frequent diagnoses in hospitalized children are bronchiolitis and pneumonia, but occasionally HMPV may also cause severe illnesses that require treatment at intensive care units 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent diagnoses in hospitalized children are bronchiolitis and pneumonia, but occasionally hMPV may also cause severe illnesses that require treatment at intensive care units (17,18).…”
mentioning
confidence: 99%